Energy-irrigation nexus in South Asia: improving groundwater conservation and power sector viability - Shah, Tushaar; Scott, Christopher A.; Kishore, Avinash; Sharma, Abhishek (International Water Management Institute, 2004)
In the highly populated South Asian region, where pump irrigation has gained predominance over gravity-flow irrigation in recent decades, the fortunes of groundwater and energy economies are closely tied. Little can be done in the groundwater economy that will not affect the energy economy, and the struggle to make the energy economy viable is frustrated by the often violent opposition from the farming community to the rationalization of energy prices. As a result, the region's groundwater economy has boomed at the expense of the development of the energy economy. This report suggests that this does not have to be so; and the first step to evolving approaches to sustaining a prosperous groundwater economy with a viable power sector is for the decision makers in the two sectors to talk to each other, and jointly explore better options for energy-groundwater co-management which, the authors suggest, have so far been overlooked.